Experiential Learning in Clinical Education Guided by the Kolb’s Experiential Learning Theory - Nurunnabi, Abu Sadat Mohammad; Rahim, Riffat; Alo, Dilara; Mamun, Abdullah Al; Kaiser, Amir Mohammad; Mohammad, Taneem; Sultana, Farhana (International Journal of Human and Health Sciences (IJHHS), 2022)
In clinical education, experiential learning can be an important component of the instructional process. We know that in medical college hospitals, learning that takes place at patient’s bed side or in wards is totally different from learning that takes place in the classroom. Each patient encounter is a new learning experience where new information is internalized and applied in the context of previous knowledge and experience. This emphasizes the importance of experiential learning where medical students should have the opportunity to effectively and efficiently internalize, process, and apply new information. However, a major global challenge for the clinical education is the workload placed on the clinical teachers, who struggle to divide time between clinical, teaching, administrative, and other duties. Experiential learning helps to form an integrated approach to clinical teaching that simplifies the relationship between a physician’s clinical and educational duties and erase the distinction between teaching and patient care duties; the students are also benefited. Kolb proposed experiential learning theory, a four-stage cyclical model of knowledge development that combined individuals’ conscious recognition and transformation of experience, which was first published in 1984.Experiential learning can be applied throughout the medical educational environment by institutional development programmes, including longitudinal outcome assessment, curriculum development, student development, and faculty development. The use of experiential learning, where students are purposefully engaged in direct experience with an emphasis on reflection, increases the ability of students to develop clinical skills and competences during their clinical phase of medical education. This review paper aims to discuss how experiential learning can be integrated in clinical education. International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 155-160